2011
DOI: 10.1038/nrmicro2549
|View full text |Cite
|
Sign up to set email alerts
|

Molecular aspects of bacterial pH sensing and homeostasis

Abstract: Diverse mechanisms for pH-sensing and cytoplasmic pH homeostasis enable most bacteria to tolerate or grow at external pH values that are outside the cytoplasmic pH range they must maintain for growth. The most extreme cases are exemplified by the extremophiles that inhabit environments whose pH is below 3 or above 11. Here we describe how recent insights into the structure and function of key molecules and their regulators reveal novel strategies of bacterial pH-homeostasis. These insights may help us better t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
746
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 854 publications
(764 citation statements)
references
References 149 publications
12
746
0
6
Order By: Relevance
“…The molar growth yields of B. pseudofirmus OF4 cells on malate further revealed that the c 12 mutants have a considerably reduced capacity to grow on limiting malate at high pH. Our results demonstrate that the mutant ATP synthases with either c 12 or c 13 can support ATP synthesis, and also underscore the critical importance of an alanine motif with c 13 ring stoichiometry for optimal growth at pH >10. The data indicate a direct connection between the precisely adapted ATP synthase c-ring stoichiometry and its ionto-ATP ratio on cell physiology, and also demonstrate the bioenergetic challenges and evolutionary adaptation strategies of extremophiles.…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…The molar growth yields of B. pseudofirmus OF4 cells on malate further revealed that the c 12 mutants have a considerably reduced capacity to grow on limiting malate at high pH. Our results demonstrate that the mutant ATP synthases with either c 12 or c 13 can support ATP synthesis, and also underscore the critical importance of an alanine motif with c 13 ring stoichiometry for optimal growth at pH >10. The data indicate a direct connection between the precisely adapted ATP synthase c-ring stoichiometry and its ionto-ATP ratio on cell physiology, and also demonstrate the bioenergetic challenges and evolutionary adaptation strategies of extremophiles.…”
mentioning
confidence: 62%
“…In the extreme alkaliphile Bacillus pseudofirmus OF4, the glycine motif is replaced by AxAxAxA. We performed a structural study on two mutants with alanine-to-glycine changes using atomic force microscopy and X-ray crystallography, and found that mutants form smaller c 12 rings compared with the WT c 13 . The molar growth yields of B. pseudofirmus OF4 cells on malate further revealed that the c 12 mutants have a considerably reduced capacity to grow on limiting malate at high pH.…”
mentioning
confidence: 99%
“…Changes in pH in disrupt the transmembrane proton motive force, which is a very important process because it drives the bioenergetics network (Krulwich et al 2007). Living cells are critically dependent upon pH homeostasis because most proteins have distinct pH ranges for function (Krulwich et al 2011). In this regard, a reduction in the specific activity of the enzymes hexokinase and acetate kinase, as well as the overall glycolytic activity, occur at pH <5 (Warth 1991).…”
Section: Discussionmentioning
confidence: 99%
“…A K þ transporting ATPase complex (CCALI_01552-54) may serve to reduce the electrical component (DC) of the proton motive force and facilitate the acidophilic phenotype. However, as expected from its narrow pH tolerance range, nearly all of the well-known inducible pH homeostasis mechanisms (Jain and Sinha, 2009;Krulwich et al, 2011) were missing from the genome. There was no evidence of glutamate, arginine or lysine decarboxylases for dealing with acid stress, nor of a urease system, agmatine deiminase or malolactic fermentation.…”
Section: Secondary Metabolism Featuresmentioning
confidence: 93%